Hubungan Perilaku Pemberian Makanan Pendamping Asi (Mp-Asi) Dengan Status Gizi Bayi Usia 6-24 Bulan Di Wilayah Kerja Puskesmas Satelit Kota Bandar Lampung - Winda Puspita Sari; Dian Isti Angraini (Medula, 2022)
After the baby agrees 6–12 months breastfeeding is no longer enough to meet nutrition. Inadequate fulfillment of nutrition will result in poor nutritional status of children. The impact of malnutrition status will cause an increase in physical growth and intelligence development as well as a decrease in endurance which results in an increase in mortality in infants. One cause of malnutrition is the help of parents in providing complementary feeding. This study aims to determine the relationship between the behavior of complementary feeding with the nutritional status of infants aged 6–24 months in working area of ​​the Bandar Lampung Satelit Health Center. This research uses quantitative method with cross sectional approach. The sample consisted of 64 mothers who had babies aged 6–24 months in working area of ​​Bandar Lampung Satelit Health Center. Sampling was done by consecutive sampling and the data were analyzed by chi square test. As many as 45 infants (70.3%) had good nutritional status and 19 (29.7%) infants had undernourished status. A total of 25 people (39.1%) had good complementary feeding behavior, while a total of 39 people (60.9%) have poor complementary feeding giving behavior. Statistically, complementary feeding giving behavior is related to infant nutritional status with p value = 0,000. Based on this study, we can concluded that there is a relationship between maternal behavior in the provision of complementary feeding and nutritional status of infants aged 6–24 months in working area of ​​Bandar Lampung Satelit Health Center.